MY WAY TO CARVING (from unknown artist's memories) - Крук, Г. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
These are the memoirs by Hryhorii Kruk (1911-1981), a famous Ukrainian sculptor from the diaspora, published in the edition of Toronto already after the artist’s death. Giving them, we preserve the author’s style.